2013
DOI: 10.1186/1472-6963-13-461
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist care and the management of coronary heart disease: a systematic review of randomized controlled trials

Abstract: BackgroundSecondary prevention is important for reducing both mortality and morbidity of patients with coronary heart disease (CHD). Pharmacists can provide medication and also work on disease management for patients with CHD. This review has been carried out to evaluate the role of pharmacist care on mortality, morbidity, and the CHD management.MethodsThe PubMed, MEDLINE, EMBASE, Web of Science and Cochrane Central Register of Controlled Trials databases were searched for randomized controlled trials (RCTs) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 17 publications
(52 reference statements)
0
22
1
7
Order By: Relevance
“…It merits mentioning that there are data that provider visits need not solely be with physicians. A recent review of pharmacist care in the management of CAD analyzed five studies in which pharmacist counseling not only resulted in greater adherence to secondary prevention therapies but, in some studies, lower cholesterol levels, lower blood pressure measurements, and lower rates of cardiovascular events [43]. Similarly, more intensive and frequent cardiac rehabilitation visits after MI has been associated with approximately 40% increase in medication adherence, as well as lower LDL-C and greater rates of smoking cessation [44].…”
Section: Health Team and System-related Factorsmentioning
confidence: 99%
“…It merits mentioning that there are data that provider visits need not solely be with physicians. A recent review of pharmacist care in the management of CAD analyzed five studies in which pharmacist counseling not only resulted in greater adherence to secondary prevention therapies but, in some studies, lower cholesterol levels, lower blood pressure measurements, and lower rates of cardiovascular events [43]. Similarly, more intensive and frequent cardiac rehabilitation visits after MI has been associated with approximately 40% increase in medication adherence, as well as lower LDL-C and greater rates of smoking cessation [44].…”
Section: Health Team and System-related Factorsmentioning
confidence: 99%
“…Indeed, research has demonstrated the effectiveness of pharmacistprovided disease management activities, including for hypertension. [4][5][6][7][8][9][10] Specific to hypertension, a recent systematic 94 Circulation July 14, 2015…”
Section: Editorial See P 75 Clinical Perspective On P 100mentioning
confidence: 99%
“…Systematic reviews of the impact of pharmaceutical interventions on several diseases are available in the literature . As a function of the scarcity of studies in this field, most such reviews included fewer than 10 studies.…”
Section: Resultsmentioning
confidence: 99%